(untitled) (Journal of the College of Basic Education, 2023)
Objective: The study aims to find the relationship between students’ knowledge toward nutritional facts labeling and their demographic characteristics. Methodology: Descriptive design study was carried out in the Colleges of Baghdad City )College of Arts and College of Nursing) during 1st June 2010 to 1th July 2011. Random sample was selected from [200] student college in Baghdad City and the study instrument was questionnaire for data collected by using direct interview. The data were analyzed by using descriptive statistical approach [frequency, percentage, and mean of score] and inferential data analysis approach [chi- square]. Results: The finding of the study was indicated that the large number of students had enough knowledge about nutritional facts labeling. Recommendation: The study recommended that students’ knowledge about nutritional fact labeling improved by education program at all universities in Iraq.